Efek Metode Blansing dan Suhu Pengeringan Terhadap Mutu Tepung Ubi Jalar (Ipomoea batatas L.) - Sabahannur, St; Netty, Netty; Ralle, Andi; Ikhsan, Muhammad (Universitas Pattimura, 2023)
Sweet potato is the sixth food crop in the world, containing high amounts of carbohydrates with a low glycemic index value. Sweet potatoes are easily damaged during storage, so their shelf life is short. Sweet potato processing into flour is an alternative to sweet potato preservation. Blanching and drying are two processing steps that have an impact on the quality of sweet potato flour. The study aimed to examine the effect of the blanching method and drying temperature on the quality of sweet potato flour. The study used a two-factor Completely Randomized Design. The first factor was the blanching method, which had two levels: steamed blanching and blanching by boiling. The second factor was the drying temperature of 50°, 60°, and 70°C. The results showed that sweet potatoes blanched using boiling and dried at 60°C produced good-quality sweet potato flour based on a yield value of 36.12%, carbohydrates of 70.44%, bulk density of 0.52 g/mL, moisture content of 0.34% and ash content of 3.3%. The assessment results of the color and aroma of sweet potato flour using the scoring method produced a yellowish-white flour color (score of 3.53) and a slightly distinctive aroma of flour (score of 3.46).